Measurement of clinical change in progressive systemic sclerosis: a 1 year double-blind placebo-controlled trial of N-acetylcysteine. Issue 4 (August 1979) - Furst, D E; Clements, P J; Harris, R; Ross, M; Levy, J; Paulus, H E
Abstract : N-acetylcysteine was employed as a therapeutic agent in a 1-year, parallel, double-blind, placebo-controlled, prospective study of 22 patients with progressive systemic sclerosis (PSS). Patients were closely followed-up and were extensively evaluated at baseline, 6 and 12 months. Most parameters remained unchanged during 1 year of study in both the NAC and placebo groups, which showed the need for prolonged studies of drugs in PSS if definitive results are to be obtained. Over the year of the study the diffusing capacity decreased in both groups, while several other parameters measured both increased and decreased. Several simple measures of function and skin distensibility were tested and two (oral aperature and handspread) were reproducible and sensitive enough to measure moderate changes of disease activity. They may be useful in future trials of drug effect in PSS.